THE PARTITIONING OF NA BETWEEN MELILITE AND LIQUID: PART I. THE ROLE OF CRYSTAL CHEMISTRY AND LIQUID COMPOSITION - Beckett J.R.; Stolper E. (My University, 2000)
The partitioning behavior of Na between melilite and liquid has been determined from the compositions of coexisting phases produced in slowly cooled (1°C/h) dynamic crystallization experiments on a single bulk composition corresponding to an average type B inclusion from the Allende C3V carbonaceous chondrite. Distribution coefficients (DNaMel/L) were determined over the entire range of melilite + spinel crystallization. For low Na concentrations (0.2-0.33 wt% Na2O in the melts), sodium is incompatible in gehlenitic melilite (e.g., DNaMel/L = 0.4 at XAkMel = 0.22) but compatible in melilite more magnesian than XAkMel ~ 0.50 (e.g., DNaMel/L = 1.5 at XAkMel = 0.65). Variations in DNaMel/L with composition for our experiments can be understood in terms of a simple thermodynamic model for the partitioning of Na between melilite and melt. The compositions of both melt and solid are important in determining the value of DNaMel/L and, with an empirical correction for Na2O in the melt, DNaMel/L for experimentally determined partition coefficients in this study and in the literature can be predicted with an average deviation of 15% for melts containing up to 8 wt% Na2O. The partitioning of Na between melilite and plagioclase in low-Na, Fe-free systems can also be predicted using a semiempirical model for the exchange equilibrium.